The Influence of Handbook Made By KUKIS Program to Student English Vocabulary - jabri, Umiyati; Ismail, Ismail; Assidiq, Ilham; Samad, Ita Sarmita; Setiawan, Ahmad Fajrin (Universitas Muhammadiyah Enrekang, 2023)
This study examines the effect of utilizing a handbook developed within the KUKIS program on enhancing students' English vocabulary. Research was conducted in SD Negeri 110 Lura with a population were students of V and VI. The research was carried out using experimental research with a Pre-experimental Research Design with The One-Shot Case Study. Data of research statistical was analyzed by the model of simple linear regression. Results of the analysis indicated that the correlation coefficient value was 0.87 and the determination coefficient value was 0.75. Based on the result, it can be assumed that there is a very high positive linear influence of the handbook made by the KUKIS Program on students’ English vocabulary at English learning with a contribution of 76% and equation regression is Y =0.75X+ 7.06. These outcomes underscore the substantial positive impact of integrating the KUKIS Program handbook in enhancing students' English vocabulary in an instructional context.